Hubungan Pendampingan Orang Tua dengan Tingkat Kecemasan Anak Prasekolah pada Prosedur Pemasangan Infus di RSUD Awet Muda Narmada - Sukaram; Iwan Zulkarnaen (Gema Cendekia Institute, 2025)
Hospitalization is often a distressing experience for preschool children, particularly when they are exposed to invasive nursing procedures such as intravenous (IV) insertion. At this developmental stage, children have limited cognitive ability to understand the purpose of medical interventions, which may lead to fear, anxiety, and negative behavioral responses; high anxiety during IV insertion can result in resistance, prolonged procedures, and increased stress for both children and healthcare providers, highlighting the importance of effective non-pharmacological approaches in pediatric nursing care. Parental accompaniment is widely recognized as a supportive strategy that provides emotional comfort and a sense of security, helping children feel safer, improve coping abilities, and cooperate more effectively during nursing interventions, although its implementation during IV insertion is not always consistent in clinical practice. This study aimed to examine the relationship between parental accompaniment and anxiety levels among preschool children undergoing IV insertion at Awet Muda Narmada Regional General Hospital, Indonesia, using a quantitative correlational design involving preschool-aged children who received IV therapy during hospitalization. Children’s anxiety levels were assessed through an observational anxiety measurement tool, while parental accompaniment was documented based on parental presence during the procedure, and the data were analyzed using appropriate statistical methods. The findings showed that preschool children accompanied by their parents during IV insertion experienced lower anxiety levels, demonstrated calmer behavior, and showed better cooperation compared to those who were not accompanied. These results indicate that parental accompaniment plays a significant role in reducing anxiety among preschool children during IV insertion and support the application of family-centered and atraumatic care practices in pediatric nursing services at Awet Muda Narmada Regional General Hospital.